1969
DOI: 10.1115/1.3591752
|View full text |Cite
|
Sign up to set email alerts
|

Vibratory Bending of Damped Laminated Plates

Abstract: The natural frequencies and associated composite loss factor have been determined for a finite-length laminated plate having alternate elastic and viscoelastic layers. Partial differential equations in terms of the variables of the plate are derived and, with the loading equation for a freely vibrating plate, a set of simultaneous partial differential equations is formed. Of two solutions considered the first is general and the second satisfies the boundary condition for a simply supported plate. In both cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Ross, Ungar, and Kerwin, the first to study the flexural vibration of a sandwich configuration [18,19], proposed an effective complex flexural stiffness which can be used to determine the modal parameters of a sandwich beam using the equations and the wavenumbers corresponding to an Euler-Bernoulli beam. DiTaranto [20,21] and Mead and Markus [22,23] demonstrated that the flexural motion of a sandwich beam is governed by a sixth-order linear homogeneous differential equation. Rao derived a similar equation of motion using Hamilton's principle [24].…”
Section: Analytical Models For the Dynamic Response Of Laminated-glasmentioning
confidence: 99%
See 3 more Smart Citations
“…Ross, Ungar, and Kerwin, the first to study the flexural vibration of a sandwich configuration [18,19], proposed an effective complex flexural stiffness which can be used to determine the modal parameters of a sandwich beam using the equations and the wavenumbers corresponding to an Euler-Bernoulli beam. DiTaranto [20,21] and Mead and Markus [22,23] demonstrated that the flexural motion of a sandwich beam is governed by a sixth-order linear homogeneous differential equation. Rao derived a similar equation of motion using Hamilton's principle [24].…”
Section: Analytical Models For the Dynamic Response Of Laminated-glasmentioning
confidence: 99%
“…Thus, the behavior of the interlayer is modeled by means of the shear modulus in the time domain or in the frequency domain [5][6][17][18][19][20][21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They assumed that the wave motion in a constrained layer configuration can be described by a fourth-order differential equation. Ditaranto [23,24] and Mead and…”
Section: Introductionmentioning
confidence: 99%